Weaving lives of the people of Aurora through landscape design of a Coco-Sabutan Immersion Camp - Balbuena, Caroline M. (Quezon City College of Architecture, University of the Philippines Diliman, 2014)
Aiming to promote and strengthen the declining industry of coconut and sabutan in Aurora Province, this thesis explored the possible application of landscape architecture in planning and designing an eco-tourism-based coco-sabutan camp. Using various research methodologies such as descriptive surveying, site mapping, and quasi-qualitative place analysis, different environmental and socio-cultural factors were determined and considered in the design development. With the use of the research findings, a concept for the new coco-sabutan immersion camp was formulated, as inspired by the interweaving pattern of the industry, culture, and the lives of the people of Aurora.
Thesis (Bachelor of Landscape Architecture)--University of the Philippines Diliman
Keywords: Coconut industry -- Aurora(Quezon) .